Development of determination method and study of piperidinium 2-((5-(furan-2-yl)-4-phenyl-4H-1,2,4-triazol-3-yl)thio) acetate in milk of cows in 12 hours after administration - B. O. Varynskyi; Ye. O. Karpun; V. V. Parchenko; O. I. Panasenko; B. P. Kyrychko; І. V. Hyrenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The purpose of our work was developing the HPLC-MS method for determining piperidinium 2-((5-(furan-2-yl)-4-phenyl-4H-1,2,4-triazol-3-yl)thio) acetate and researching the presence of residual amounts of piperidinium 2-((5-(furan-2-yl)-4-phenyl-4H-1,2,4-triazol-3-yl)thio) acetate in cow’s milk in 12 hours after injection.